The crossroads of Leber hereditary optic neuropathy and autosomal dominant optic Atrophy: Clinical profiles of patients with coexisting pathogenic genetic variants - Mohammed A. Halawani; Nooran O. Badeeb (American Journal of Ophthalmology Case Reports)
Purpose: Leber Hereditary Optic Neuropathy (LHON) and Autosomal Dominant Optic Atrophy (ADOA) are hereditary optic neuropathies characterized by mitochondrial dysfunctions causing destruction to the retinal ganglion cells and their axons, painless bilateral vision loss and symmetrical temporal pallor of the optic nerve. We present six intrafamilial cases with different manifestations of LHON and/or ADOA and their genetic variant profiles. Observations: Two brothers and their father had symptomatic bilateral vision loss, two sisters were asymptomatic, and the mother had left eye vision loss due to solar retinopathy; accompanied with headaches. Five of the patients had normal anterior and posterior segment exam aside from the affected optic nerves. The family pedigree showed an unaffected first generation and an affected male in the second generation. In the third generation, an affected male (the father in this family), diagnosed with optic atrophy due to OPA1 c.2383C > T variant, married a woman (the mother) carrying the LHON MT-ND4 m.11778G > A variant. Their offspring were one unaffected daughter, one affected daughter and two affected sons harboring both LHON and ADOA pathogenic variants inherited from their parents. Conclusion and importance: Mitochondrial optic neuropathies, which result in loss of retinal ganglion cells, are a substantial cause of visual impairment. Herein, we report two cases of combined LHON- and ADOA-causing pathogenic variants in two brothers, in addition to the genetic and ophthalmologic profile of their parents and two sisters.